Intelligent robust controller for semi active suspension system - Zeinali, Mohammadjavad (2012)
A variety of semi-active suspension studies have been researched on decreasing the energy consumption and improving the system performance as fully active suspension systems because of the expense of fully active suspension systems for its actuators and execution equipments. However, the fully active suspension systems are much more powerful than semi active suspension. This project has proposed an intelligent robust controller for semi active suspension due to its applications on automotive industry using Magnetorheological (MR) damper. The entire model has been simulated in Matlab/SIMULINK environment and the results are gathered to compare the influences of the different controllers on ride comfort and handling performance. Four different controllers; PID, Fuzzy, Fuzzy PD+I and Fuzzy PID controller with parallel structure were implemented into the system also two different models of MR damper, polynomial and Adaptive-Network-based Inference System (ANFIS) model, were studied to simulate the shock absorber. The results illustrate that the Fuzzy PD+I controller and Fuzzy PID controller with parallel structure have successfully reduced the effects of road profile as a disturbance. The best results are owned by Fuzzy PID controller with parallel structure because of better ride comfort and handling performance.